A business case for digital transformation of a Malaysian-based university - Zulfikar, M.Wildan; Hashim, Amirul Idham; Ahmad Umri, Haliq Ubaid; Ahmad Dahlan, Abdul Rahman (IEEE Explore, 2018)
The space of higher education has been receiving enough disruptions lately from the vast amount of advancements in technology. They are forced to adapt to the dynamic demands,tools, and other technological changes that can be overwhelming. This adaptation to technological changes is often referred to as digital transformation, which is unavoidable, unless if the institution is ready to be deemed irrelevant. This paper will start the discussion on the topic of this transformation; the role of university, why the transformation is needed, and what are the challenges that come with such transformation.